Prevalence and Correlated Factors of Urinary Incontinence in Geriatrics - Adriel John Junior Purba; Syah Mirsya Warli; Dhirajaya Dharma Kadar; Putri Charani Eyanoer (Sumatera Medical Journal, 2023)
Background: Urinary incontinence is involuntary or uncontrollable urine passing. This is very disruptive, it causes a lot of problems and is often seen as an embarrassing thing. The prevalence of urinary incontinence was found to increase with age. Objective: This research aimed to determine the prevalence and factors associated with the incidence of urinary incontinence in geriatric patients at the Haji Adam Malik General Central Hospital and the University of North Sumatera Hospital. Methods: This type of research is an analytic observational study with a cross-sectional design. The research sample is determined by consecutive sampling technique using a questionnaire as primary data. Results: Out of 100 respondents, 22 geriatric patients experienced urinary incontinence, with the majority experiencing moderate severity and stress urinary incontinence. Based on bivariate analysis using chi-square found gender (p=0.617), age (p=0.617), overweight (p=<0.01), diabetes mellitus (p=<0.01), hypertension (p=0.01), history of chronic cough (p=<0.01), history of pelvic surgery (p=<0.01), and history of vaginal delivery (0=0.055). Conclusion: In this study, the risk factors associated with urinary incontinence are overweight, diabetes mellitus, hypertension, and a history of chronic cough while risk factors that are not found to be associated in this study are age, sex, and history of vaginal delivery.